Health Data Linkage for Public Interest Research in the UK: Key Obstacles and Solutions - Mourby, Miranda Jane; Doidge, James; Jones, Kerina H; Aidinlis, Stergios; Smith, Hannah; Bell, Jessica; Gilbert, Ruth; Dutey-Magni, Peter; Kaye, Jane (International Journal of Population Data Science, 2019)
Introduction Analysis of linked health data can generate important, even life-saving, insights into population health. Yet obstacles both legal and organisational in nature can impede this work. Approach We focus on three UK infrastructures set up to link and share data for research: the Administrative Data Research Network, NHS Digital, and the Secure Anonymised Information Linkage Databank. Bringing an interdisciplinary perspective, we identify key issues underpinning their challenges and successes in linking health data for research. Results We identify examples of uncertainty surrounding legal powers to share and link data, and around data protection obligations, as well as systemic delays and historic public backlash. These issues require updated official guidance on the relevant law, approaches to linkage which are planned for impact and ongoing utility, greater transparency between data providers and researchers, and engagement with the patient population which is both high-profile and carefully considered. Conclusions Health data linkage for research presents varied challenges, to which there can be no single solution. Our recommendations would require action from a number of data providers and regulators to be meaningfully advanced. This illustrates the scale and complexity of the challenge of health data linkage, in the UK and beyond: a challenge which our case studies suggest no single organisation can combat alone. Planned programmes of linkage are critical because they allow time for organisations to address these challenges without adversely affecting the feasibility of individual research projects.